101 favorite play therapy techniques - Kaduson, Heidi; Schaefer, Charles E. (b, 1997)
"Building on children's natural inclinations to pretend and re-enact, play therapy is widely used in the treatment of psychological problems in childhood. 101 Favorite Play Therapy Techniques incorporates methods developed to elicit the best responses from children by therapists representing cognitive-behavioral, psychodynamic, and other orientations, and selected for their practicality, specificity, and originality. Arranged for easy reference, each bearing a succinct description and targeted application, the interventions illustrated have been used with success to address such common problems as low self-esteem and unresolved fear and anger as well as more serious difficulties arising from loss, abuse, and sexual trauma."
Includes bibliographical references.
Keywords: Play therapy